Implementasi Proxy Server Menggunakan Squid Sebagai Sistem Bandwith Monitoring dan Website Filtering (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
Computer Network Technology as a medium of data communication is currently increasing, especially on the internet network (interconnection networking) which is a complex network. The need for shared use of existing resources in the network, both software and hardware, has resulted in various developments in network technology itself. With the increasing level of demand and the increasing number of network users, they want a form of network that can provide maximum results both in terms of efficiency and increasing network security. One of the steps in monitoring and securing data servers is to use a proxy server. The proxy server in this case is a third party who acts as an intermediary between the two parties who are interconnected, in this case the local network and the internet network. The proxy server acts as a gateway to the world of the internet for each client so that data traffic can be controlled. This monitoring and blocking system was built using Squid Proxy Server.